CURRENT STATE OF THE SMALL RPAS MAINTENAN CE IN THE CZECH REPUBLIC (Perner's Contacts, 2016)
This paper summarize a current state of a small unmanned aerial vehicles maintenance at the territory of the Czech Republic. The word “small” means unmanned vehicles with the maximum take-off mass not exceeding 20 kg. A reader becomes familiar with a RPAS (Remotely Piloted Aerial Systems) maintenance issues an also with a legislation in the first part of the paper. The legislation determines requirements for their maintenance. The next part describes the current state of this type of the maintenance. The last part of the paper deals with the future of the small RPAS maintenance. There is a rough estimate of a future maintenance development in this part of the paper. There also are a possible solutions of these issues in this part. These things are there because the authors think that there is a space for a RPAS maintenance improving.
Keywords: RPAS maintenance; UAV maintenance; unmanned vehicle maintenance; maintenance in the Czech Republic; RPAS in the Czech Republic; UAV in the Czech Republic; current state of a maintenance